Identification of a novel SNP mutation causing drop-out alleles in a paternity test using combined nest and touch-down PCR with Sanger sequencing - Hongbo Wang; Botong Shi; Liang Guo; Yingnan Zou; Bo Liu; Jun Yao; Baojie Wang; Zhengdong Wang; Xin Li; Gang Mu; Fu Ren (Annals of Human Biology)
Background Short tandem repeat (STR) markers are widely used in forensic DNA analysis due to their ability to provide automated and standardised typing. However, incorrect STR typing can have a significant impact on forensic outcomes.Aim In this study, we detected drop-out alleles at the SE33 locus in a putative father-son pair using the Microreader™ 28 A ID System. This result could lead to a false conclusion of non-paternity.Subjects and methods To investigate the cause of the drop-out alleles, we developed a nest and touch-down PCR program for Sanger sequencing of the SE33 locus. Subsequently, we investigated the mutation frequency in 300 unrelated individuals and reviewed the results of 429 paternity tests.Results The results showed that the frequency of the G > T mutation at this locus was less than 0.01, which is a novel and rare mutation. Our analysis revealed a novel G > T mutation in the primer-binding region of both samples, which was a rare single-nucleotide mutation site in the Chinese population. This variation was found to be responsible for the drop-out alleles observed in the samples.Conclusion Our findings have important implications for optimising primer design and constructing DNA databases for forensic analysis.